Genetic diversity and haplogroups distributions of Kampung chickens using hypervariable-I mitochondrial DNA control region - Arifin Zein, M Syamsul; Sulandari, S (Indonesian Journal of Animal and Veterinary Sciences, 2012)
Until now no studies evaluating the position of Kampung chickens in chicken clade of Asia. Thus studies based on molecular DNA sequence hipervariable-I on Kampung chicken is needed. Molecular studies based on DNA sequences hyper variable-I of Kampong chicken was done to confirm the results of previous evaluations conducted on 15 families of local chickens of Indonesia. An analysis of 210 individuals Kampung chicken (Aceh, North Sumatra, Lampung, Banten, Central Java, Lombok, Sulawesi, Ternate, Morotai and Halmahera) resulted in 51 haplotypes derived from 62 polymorphic sites. Polymorphic sites among the highest seen at 112-397 (93.22%). The highest haplotype frequencies contained in the haplotype H-4 (36.19%), followed by H-1 (18.57%) and H-5 (10, 95%). Kampung chicken phylogeny analysis formed four haplogroups/clade from 7 references of Asian chicken clade. Four haplogroups are clade II = 84.31% (43 haplotypes), clade IIIC = 1.96% (1 haplotype), clade IIID = 3.92% (2 haplotypes), clade IV = 7.84% (4 haplotypes). The results prove of that Indonesian local and indigenous chickens were equally dominated clade II. Analysis of genetic diversity showed haplotype diversity of 0.825 Â± 0.021, nucleotide diversity of 0.00600 on average, the genetic distance between populations ranged from 0.003 to 0.011, and the genetic distance within populations ranged from 0.00395 to 0.01031. Genetic distance between individuals in all populations of Kampung chickens was significantly different (P < 0.01). Fus Fs values was negative, indicating high genetic diversity and population expansion on native chicken in Indonesia. Other important result was shown with the major haplotype spread from western to eastern Indonesia, and had strengthened the position of Indonesia as one of the centers of domestication of the chicken. Key Words: Kampung Chicken, Hypervariable-I, Control Region, Mitochondrial DNA, Haplotype, Clade